The effects of rearing temperature on reproductive conditioning of stalked barnacles (Pollicipes pollicipes) - Franco, Sofia C. (2018)
Pollicipes pollicipes (Crustacea; Pedunculata) is a delicacy on the Iberian Peninsula where, in recent years, stock shortages associated with high market value have increased interest in the aquaculture potencial of this species. Though broodstock has been maintained in captivity, detailed culture conditions are lacking.